The content and function of landscape in the text of Shukur Kholmirzayev's stories included in the collection "Bandi burgut" - Choriyev , Nurbek (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article explores Shukur Kholmirzayev and his stories. Also the theoretical views on the image of man and the surrounding nature in the Bandi Eagle collection are revealed. The primary objective of this research is to convey the essence of this masterpiece to readers and to make, even if modest, a contribution to the field of literary studies.